1996
DOI: 10.1074/jbc.271.30.17811
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Imino Intermediate in the DNA Polymerase β Deoxyribose Phosphate Excision Reaction

Abstract: A recent study demonstrated that rat DNA polymerase ␤ (␤-pol) releases 5 -deoxyribose phosphate (dRP) termini from preincised apurinic/apyrimidinic DNA, a substrate generated during certain types of base excision repair. This catalytic activity resides within the aminoterminal, 8-kDa domain of ␤-pol and occurs via ␤-elimination as opposed to hydrolysis (Matsumoto, Y., and Kim, K. (1995) Science 269, 699 -702). The latter finding suggested that the dRP excision reaction might proceed via an imine intermediate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 27 publications
(21 reference statements)
5
144
0
Order By: Relevance
“…These enzymes were evaluated because it has been shown that pol ι is involved in V-region mutagenesis in human BL2 cells [3,16,32,33], and, in addition pol λ another member of the group of BER proficient DNA polymerases [35] can serve as a backup enzyme for pol β in BER [21]. Both of these polymerases carry intrinsic dRP lyase activities that may be important in short patch BER [24,[36][37][38]. We analyzed expression of these enzymes by immunoblotting and found no significant differences in the BL2 clones studied here.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes were evaluated because it has been shown that pol ι is involved in V-region mutagenesis in human BL2 cells [3,16,32,33], and, in addition pol λ another member of the group of BER proficient DNA polymerases [35] can serve as a backup enzyme for pol β in BER [21]. Both of these polymerases carry intrinsic dRP lyase activities that may be important in short patch BER [24,[36][37][38]. We analyzed expression of these enzymes by immunoblotting and found no significant differences in the BL2 clones studied here.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of LP-BER vs. SN-BER may thus depend on, among other factors, the state of the 5′-dRP terminal moiety. With unaltered aldehyde group in deoxyribose Polb could carry out SN-BER by excising the 5′-dRP [17,81]. On the other hand, LP-BER is necessary when the AP sites are further oxidized by ROS, and the resulting 5′ blocking groups after cleavage of the DNA strand by APE could not be removed by Polb's 5′ end cleaning lyase activity.…”
Section: Two Basic Modes Of Ber: Sn-vs Lp-bermentioning
confidence: 99%
“…In mammalian cells, most dRp excision is attributable to Polb (Sobol et al, 1996), specifically its amino-terminal 8-kilodalton domain (Matsumoto and Kim, 1995). In this process, lysine-72 performs a nucleophilic attack on the C1-carbonyl carbon of the 5'-terminal AP site, which forms a Schiff base intermediate between the enzyme and the DNA (Feng et al, 1998;Piersen et al, 1996) (Figure 2). belimination breaks the 3' phosphodiester, and the enzyme-deoxyribose complex is hydrolyzed to yield the free abasic-5-phosphate residue.…”
Section: Dual Pathways Of Bermentioning
confidence: 99%